2009
DOI: 10.1177/1538192709343102
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a College Education: The Psychological Experiences of Latina/o Community College Students

Abstract: This study examines the psychological and subjective experiences of Latina/o community college students. The impact of these experiences on their persistence toward achieving their education goals is also examined. Qualitative interviews with 15 community college students yielded eight themes: Overcoming personal and social challenges, maturation, self-discovery and college adjustment, self-efficacy, continuously strategizing, sense of purpose, perception of faculty, perception of advisors, and guided and groo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 22 publications
2
61
1
Order By: Relevance
“…For instance, research by Barnett (2011) brought attention to the value of validating mentoring relationships that develop informally between undergraduate students and instructors. In contrast to prior reviews, we found an increasing focus of mentoring efforts centering specialized or targeted student populations, including African American students (e.g., Griffin, 2013), Latina/o students (e.g., Tovar, 2014;Zell, 2009) and American Indian/Alaskan Native students (e.g., Guillory, 2009). At the same time, our review also identified mentoring studies that were more global, serving broader undergraduate populations such as first-year students.…”
Section: Description Of Reviewed Mentoring Scholarshipcontrasting
confidence: 72%
See 4 more Smart Citations
“…For instance, research by Barnett (2011) brought attention to the value of validating mentoring relationships that develop informally between undergraduate students and instructors. In contrast to prior reviews, we found an increasing focus of mentoring efforts centering specialized or targeted student populations, including African American students (e.g., Griffin, 2013), Latina/o students (e.g., Tovar, 2014;Zell, 2009) and American Indian/Alaskan Native students (e.g., Guillory, 2009). At the same time, our review also identified mentoring studies that were more global, serving broader undergraduate populations such as first-year students.…”
Section: Description Of Reviewed Mentoring Scholarshipcontrasting
confidence: 72%
“…Exceptions include work by Corso and Devine (2013), Crisp (2009;, and Zell (2009). Most studies appeared to be conducted at Predominantly White Institutions (PWIs), with relatively few focused on the experiences of students at Minority Serving Institutions.…”
Section: Description Of Reviewed Mentoring Scholarshipmentioning
confidence: 99%
See 3 more Smart Citations